Treg cell therapy manufacturability: current state of the art, challenges and new opportunities - Stoops, Janelle; Morton, Tara; Powell, James; Pace, Amanda L.; Bluestone, Jeffrey A. (Frontiers in Immunology, 2025)
Autologous cell therapy is a revolutionary new paradigm in medicine. Significant advancements in personalized therapeutic treatments with engineered T cells have been seen across the immuno-oncology markets. The global market is expanding as new cell types treat other conditions, like autoimmunity and transplant rejection. Key to the success of these novel cell therapies is manufacturability; ensuring robust processes that can reliably deliver treatments that meet the medical needs. Using the expertise and experience of the current state of Regulatory T cell (Treg) manufacturing at Sonoma Biotherapeutics as a prototypical case, we review manufacturing challenges and opportunities to ensure success.